Microwave Heating (IntechOpen, 2023)
More than 80 years of experience in the practical application of electromagnetic energy in various fields of human activity (industry, agriculture, science, medicine, etc.) suggests that microwave heating is an effective application of electromagnetic energy. This book presents the latest investigations on the applications of microwave energy and the effects of microwave radiation on various materials and mediums. Divided into two sections on thermal and nonthermal effects, this volume contains eight chapters that examine the use of microwave energy to extract bioactive compounds from plant materials, for rock-breaking operations, to synthesize functional dyes and nanomaterials, and more.